The role of elevated depressive symptoms in the incident mild cognitive impairment in China: a 9-year prospective cohort study of middle-aged and older Chinese adults (2011–2020) - Gao, Shuqing; Xiao, Libin; Lv, Jie; Fan, Jingyi (Frontiers in Psychiatry, 2025)
BackgroundAlthough depressive symptoms are suspected to influence cognitive health, prospective evidence linking depressive symptoms to mild cognitive impairment (MCI) is scarce within large-scale Chinese cohorts. This study sought to analyze the graded association between initial depressive symptom severity and subsequent MCI risk in middle-aged and older adults in China, as well as to assess whether this relationship was moderated by other underlying factors.MethodsUsing data from the China Health and Retirement Longitudinal Study (CHARLS, 2011–2020), we included 9,461 participants aged ≥45 without baseline MCI. Depressive symptoms were assessed using the CESD-10 scale and categorized as none (<10), mild–moderate (10–20), or severe (≥21). Incident MCI was identified based on standardized criteria. Data analysis was performed using Cox proportional hazards regression models, which incorporated restricted cubic splines to flexibly model potential non-linear relationships. This primary analysis was further supplemented by comprehensive subgroup and sensitivity analyses to assess the heterogeneity of treatment effects and the robustness of the findings.ResultsDuring the nine-year follow-up period, a total of 1,276 new cases of MCI were documented. Analysis by depressive symptom severity revealed a graded increase in MCI risk relative to the asymptomatic reference group. In the fully adjusted model, participants with mild-to-moderate depressive symptoms exhibited a significantly increased risk of MCI (HR=1.363, 95%CI: 1.205–1.542, p<0.05), while a more pronounced risk elevation was observed in those with severe symptoms (HR=1.468, 95%CI: 1.123–1.918, p<0.05). Furthermore, each 1-SD (5.83 points) increase in CES-D score was associated with a 2.90% higher risk of MCI (HR=1.029, 95% CI: 1.020-1.039, p<0.001). Restricted cubic splines confirmed a significant linear dose-response relationship (p for nonlinear=0.419). Education significantly moderated the association, with a protective effect observed in individuals with higher education. The findings remained consistent when assessed through various sensitivity analyses.ConclusionBaseline depressive symptoms are independently and dose-dependently associated with higher MCI risk in Chinese adults aged 45 and above. Education serves as a significant moderator. Integrating depression screening into MCI prevention strategies is recommended, particularly in less-educated populations.